2023
DOI: 10.3390/ijerph20043588
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Physical Exercise Effects on Anxiety in Older Adults during the COVID-19 Lockdown: An Analysis of the Mediating Role of Psychological Resilience and the Moderating Role of Media Exposure

Abstract: The purpose of this study was to explore the effects of physical exercise on anxiety in older adults during the COVID-19 pandemic lockdown, as well as the mediating role of psychological resilience and the moderating role of media exposure. An online questionnaire was used to survey older adults in Chengdu, Southwest China. A total of 451 older adults aged 60 years and older participated in the study (209 males and 242 females). The results suggest that physical exercise negatively influenced anxiety symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…In order to improve psychological resilience, resilience in psychological capital can assist elderly people living alone in building up psychological resources through physical activity. This will enable them to bounce back quickly from setbacks when confronted with unfavorable information, such as reminders of impending death ( Xin and Ma, 2023 ). The psychological capital sense of hope also assists the elderly living alone to maintain physical health through tai chi exercise, lessen fear and worry about death and future life, and develop optimism for the future ( Peh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to improve psychological resilience, resilience in psychological capital can assist elderly people living alone in building up psychological resources through physical activity. This will enable them to bounce back quickly from setbacks when confronted with unfavorable information, such as reminders of impending death ( Xin and Ma, 2023 ). The psychological capital sense of hope also assists the elderly living alone to maintain physical health through tai chi exercise, lessen fear and worry about death and future life, and develop optimism for the future ( Peh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms behind the effects of exercising on psychological health in older adults have been less studied so far [5,44]. In a study by Zhang et al, depression and sleep quality appeared to mediate the chain effect between exercise and cognition in patients with type 2 diabetes mellitus.…”
Section: Mechanisms Underlying the Psychological Benefits Of Exercisingmentioning
confidence: 99%
“…An online survey study during the pandemic lockdown showed that psychological resilience was a mediator of the effects of physical exercise on anxiety. Moreover, reduced media exposure enhanced these effects [5]. Intensity of an exercise regimen is also important in terms of the benefits of physical training on mental health.…”
Section: Mechanisms Underlying the Psychological Benefits Of Exercisingmentioning
confidence: 99%
See 1 more Smart Citation